PEMBUATAN PETA TEMATIK PENGUASAAN TANAH DI KOTAMADYA SALATIGA BERBASIS SISTEM INFORMASI GEOGRAFIS - , FEBRIAN BAYU DWI P P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The realization of good land administration is one of Badan Pertanahan Nasionals (BPN) goal as an organization which is responsible to the implementation of land administration in Indonesia. One of the theme that is included in the land administration is land tenure. Salatiga City is facing the problem about land tenure too. Hence, a map that can show informations about land tenure in Salatiga City is critically needed. The thematic map is created by using a GIS software, ArcMap. All of the spatial datas are collected from BPN, while its attribute datas are collected by the survey of land tenure in Salatiga City. That attribute datas are added to the attribute table of land tenures data. Then, a layouting process is done, include classification and defining symbology. It is done based on the rule from BPN. The result of this study is a land tenure map of Salatiga City. Its scale is 1 : 15.000. This map then become data that is stored by BPN in order to implement land administration in Salatiga City.